Citizenship, learning and social inclusion - Viktor Vesterberg (European Journal for Research on the Education and Learning of Adults)
The aim of this article is to gain knowledge about how people engaged in EU-funded social initiatives targeting poor EU migrants in Sweden reason about the meaning, hardships, and possibilities they ascribe to the concept of social inclusion. The empirical material consists of a key policy and interviews with staff involved in these social initiatives. The analytical approach is constructionist, inspired by Foucault, focusing on how target groups are constructed, problematised and governed as learners not yet socially included in society or the labour market. In the concluding discussion, the results are discussed in relation to Levitas’ thoughts on social inclusion. Key results indicate that discourses on the national and EU level can both facilitate and hinder learning and social inclusion for vulnerable citizens. The article concludes that free mobility within the EU makes belonging and responsibility a complex issue for those engaged in learning for social inclusion.